Systematic Literature Review: Preservasi Tacit Knowledge dalam Komunitas Literasi Informasi - Azhari, Fadillah Derra; Wibowo, Muhammad Prabu (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2026)
Tacit knowledge is implicit knowledge that plays a crucial role in experiential learning within information literacy communities, yet it is difficult to preserve due to its intangible nature. This study aims to identify transfer mechanisms, preservation strategies, and factors contributing to the vulnerability of tacit knowledge in volunteer-based communities. The study employs a Systematic Literature Review (SLR) following PRISMA 2020 guidelines using the Scopus database. A total of 10 articles were analyzed through qualitative thematic synthesis. The findings show that tacit knowledge transfer occurs through shared practices, mentoring, and experience-based learning. Preservation strategies include narrative documentation, reflective practices, and community strengthening. The vulnerability of tacit knowledge is influenced by weak documentation, high member turnover, and dependence on individuals. These findings highlight that preserving tacit knowledge requires strengthening social interaction and collective practices, not merely digitalization.